2017
DOI: 10.14569/ijacsa.2017.080116
|View full text |Cite
|
Sign up to set email alerts
|

Towards Empowering Hearing Impaired Students' Skills in Computing and Technology

Abstract: Abstract-Studies have shown that deaf and hearing-impaired students have many difficulties in learning applied disciplines such as Medicine, Engineering, and Computer Programming. This study aims to investigate the readiness of deaf students to pursue higher education in applied sciences, more specifically in computer science. This involves investigating their capabilities in computer skills and applications. Computer programming is an integral component in the technological field that can facilitate the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…The results of this research are consistent with previous research that vocational training or skills help the students with hearing impairment more stable and confident and provide them more chances to get decent employment (Abuzinadah, et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…The results of this research are consistent with previous research that vocational training or skills help the students with hearing impairment more stable and confident and provide them more chances to get decent employment (Abuzinadah, et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…It is important to note that not all academic subject majors in Saudi universities are available for DHH students. The availability of subject majors varies yearly at some universities depending on the policies of the academic departments (Abuzinadah et al., 2017; King Saud University, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the quantity of hard of hearing students who are going to colleges and universities has expanded of late, a few investigations have demonstrated that most hard of hearing understudies don't complete their higher studies on account of a few challenges [2]. These problems range from the inability to hear either mostly or entirely, to the absence of special facilities to support them in overwhelming the personal and social barriers they meet due to hearing deficiency or loss or at least permit them to develop their learning proficiency as fast as their peers [3]. Subsequently, viable technological support is fundamental to improve the learning climate of hard of hearing-and hearing-impaired students.…”
Section: Introductionmentioning
confidence: 99%